2018
DOI: 10.3389/fmicb.2018.02599
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Antibiotic Resistant Bacteria During Conventional and Advanced Wastewater Treatment, and the Disseminated Loads Released to the Environment

Abstract: The occurrence of new chemical and microbiological contaminants in the aquatic environment has become an issue of increasing environmental concern. Thus, wastewater treatment plants (WWTPs) play an important part in the distribution of so-called new emerging pathogens and antibiotic resistances. Therefore, the daily loads released by the WWTP were calculated including a model system for the distribution of these loads within the receiving water body. UV-, as well as ozone-treatment in separate or in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 43 publications
5
67
0
Order By: Relevance
“…The Student's t test was used if the data were normally distributed, to identify significant differences between the treatments. In the case of a non-standard distribution, the significance was tested by a Mann-Whitney U-test [46]. The significance of the changes in the Sørensen index in comparison to the control was investigated with the two-sample t tests on the α-levels of 0.05 and 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…The Student's t test was used if the data were normally distributed, to identify significant differences between the treatments. In the case of a non-standard distribution, the significance was tested by a Mann-Whitney U-test [46]. The significance of the changes in the Sørensen index in comparison to the control was investigated with the two-sample t tests on the α-levels of 0.05 and 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were measured in technical triplicates. The specific taxonomic and resistance-directed genes in the entire bacterial community were quantified utilizing an SYBR Green qPCR approach according to Hembach et al, and Jäger et al 7,37 . Cell equivalent calculation according to Hembach et al 7,8 was performed to calculate the absolute concentration of ARG/FPB normalized to 100 mL of water sample.…”
mentioning
confidence: 99%
“…It has been shown that in many cases, sewage treatment process cannot signi cantly eliminate resistant strains or resistance genes (7). Furthermore, there are some reports that showed the increase in both antibiotic resistance rates and antibiotic resistance genes for post treatment sewage isolates (18,19). For instance, research has shown that sewage treatment process caused an increase in antibiotic resistance of E. coli to nalidixic acid, sulfamethoxazole, cephalexin and ceftriaxone (20).…”
Section: Discussionmentioning
confidence: 99%